The Development, Transformation, and Use 0f The Children's Language of Al-Quran Education Park - Koeswanti, Henny Dewi (Jurnal Ilmiah Sekolah Dasar, 2021)
Language development for children has a dynamic nature because there are many factors that can influence it. The purpose of this study is to identify various forms of language development and transformation experienced by students and students of TPA. The research method used in this research is a case study on the development, transformation, and use of language by children who are members of TPA students. This case study was conducted as an attempt to identify the phenomenology of dynamic use and development of children's language through the TPA program. The findings in the field show that there is a development, transformation, and use of a unique and interesting language that is influenced by the context of TPA as the realm of informal education based on Islamic education. This is evident from the various forms of language used by children who have developed vocabulary until they are transformed into code switching and Arabic code mixing. The use of Arabic can be seen as an opportunity because it can increase children's knowledge and vocabulary, but at the same time it can also be seen as a threat to the survival of the mother tongue and national language for children. Ideally, Indonesian and mother tongue should remain the main language for children, whether in the family, school, or when they are around their peers.